Hospital nursing care management: fellowship to strengthen professional competencies. - Gleriano, Josué Souza; Chaves, Lucieli Dias Pedreschi; Krein, Carlise; Tomaz, Wanderson Borges; Romualdo, Luciana Paiva; Santiago, Bruna Karoline de Almeida; Vidal, Pedro Henrique de Oliveira Marques; Leal, Laura Andrian (Acta Paulista de Enfermagem)
Objective: To analyze the pedagogical project of the Fellowship in Hospital Nursing Care Management in light of the recommendations for advanced nursing practices, with a focus on professional qualification. Methods: Exploratory study, qualitative approach, with documentary analysis guided by the analytical matrix of the pedagogical project, considering the elements profile and competencies; philosophical and conceptual framework; objectives; pedagogical plan; applied methodologies and evaluation criteria. Thematic analysis of data with discussion in the theoretical framework of reflective professional education, care management, and advanced nursing practices. Results: The course has 2,030 hours, structured in four modules totaling 210 theoretical hours and 1,820 practical hours. The philosophical framework is centered on the humanization of care, ethics, and social responsibility. The conceptual framework emphasizes the integration between planning, organization, execution, and evaluation of actions, with a focus on qualified care and resource efficiency. It adopts a care management framework and a concept for adult education through andragogy, problem-solving-based learning, and self-directed learning through active teaching methodologies that alternate theory and practice to develop six competencies that are transversal in teaching and learning. Assessment is formative and reflective. Conclusion: The model adopted by the Fellowship can contribute significantly to the qualification of nursing in the context of care management, aligning with the guidelines for advanced nursing practices and the demands of Health Systems.